Literacy in The Context of Communication Skills for The 21st Century Teacher Education in Primary School Students - Rahman Rahman; Wahyu Sopandi; Rani Nurcita Widya; Rasi Yugafiati (Universitas Sebelas Maret, 2019)
Communication skills to be part needs to have in the 21st century Ideally, students are memilliki high communication skills for speaking experience already gained quite a lot. However, a survey conducted by NACE (National Association of Colleges and Employeers) in 2017 indicated that as many as 67.5% of the students have low communication skills. Lack of communication skills can affect the ability to process information, the difficulty of integrating the mind and speech, and difficulty in adapting to the environment (Wood & Hartshorne, 2017, p. 1). Communicative approach into one of the efforts to overcome the lack of communication skills and the results have been tested and the effect is quite good. In addition to the communicative approach, mastery of literacy is supposed to be the solution to the problems of communication skills. This study aims to assess the role of literacy to the development of communication skills of students. Review of the literature used as a method in this study with published sources such as books, journals, or the information in the newspaper. Mastery of literacy demonstrated proficiency of each individual. Therefore, literacy is seen as an instrument that can be used to obtain and communicate information. Mastery of literacy demonstrated proficiency of each individual. Therefore, literacy is seen as an instrument that can be used to obtain and communicate information. Mastery of literacy proficiency of each individual show. Therefore, literacy is seen as an instrument that can be used to obtain and communicate information.